The RCM method is used to identify critical components and design maintenance strategies for the head truck - Nelfiyanti, .; Ahmad Shah Hizam, Md. Yasir; Azizul Qayyum, Basri; Nik Mohd Zuki, Nik Mohamed; Andry, Setiawan; Hariyanto Hadi, Kusumo (Fakultas Teknik, Universitas Muhammadiyah Jakarta, 2025)
As a private company engaged in the supply and maintenance of port equipment, PT XYZ faces operational challenges due to the high downtime of heavy equipment used. Based on 2019 data, Head Truck is the tool with the largest total disruption hours of 7,135 hours or 72% of the total downtime of the three main types of equipment, followed by RTG of 830 hours (8%) and QCC of 1,970 hours (20%). The high downtime has a direct impact on reducing operational efficiency and losses for the company. In order to improve the reliability of the Head Truck engine, an analysis was conducted using the Reliability Centered Maintenance (RCM) method which includes system identification, function and failure analysis, to the application of Failure Mode and Effect Analysis (FMEA) to find critical components and recommendations for optimal maintenance actions. The results of MTTF (Mean Time To Failure) and MTTR (Mean Time To Repair) calculations show that the crankshaft Assy component has the fastest repair time, which is an average of 2.16 hours, while the piston Assy component requires the longest repair time of around 5.75 hours. With this data, a periodic maintenance schedule is created that is adjusted to the frequency of damage and recovery time of each component, so that it can help minimize the risk of downtime and increase the operational effectiveness of the Head Truck engine.